Everywhere Equivalent 3-Braids - Stoimenow, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
A knot (or link) diagram is said to be everywhere equivalent if all the diagrams obtained by switching one crossing represent the same knot (or link). We classify such diagrams of a closed 3-braid.